The Routledge Handbook of Ecomedia Studies. - López, Antonio; Ivakhiv, Adrian; Rust, Stephen; Tola, Miriam; Chang, Alenda Y.; Chu, Kiu-wai. (Milton : Taylor & Francis Group, 2023)
The Routledge Handbook of Ecomedia Studies gathers leading work by critical scholars in this burgeoning field.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books